(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
As long as Islamic banks cannot operate in an environment that deals with traditional banking instruments based on the interest rate (bank interest) that is prohibited by Article No. (6) of the Islamic Banking Law No. (43) of 2015 which stipulates that (do not deal in any activity that carries Interest (neither taking nor giving)). Therefore it seeks to provide an alternative strategic solution within the framework of the provisions and rules of Islamic Sharia, on the basis of participating in profit and loss to avoid the method of interest taking and giving, to find investment methods to provide new financial products, such as Islamic certificates of deposit and investment funds according to the method Murabaha, speculation (Mudarabah) and sharing (Musharakah), etc; for its effective contribution to increasing the profits of Islamic banks, which is one of the main objectives behind the existence of banks, and is necessary for their survival and continuity in conducting their business. The research aims to clarify the role of the Central Bank of Iraq (CBI) in its endeavor to introduce a new investment mechanism and window (Islamic certificates of deposit (ICD)) for Islamic banks to invest their money without interest and its role in the profitability of Islamic banks. The research hypothesis is based on the existence of a positive and significant impact relationship between the investment of Islamic banks in (Islamic certificates of deposit (ICD)) and the profitability of Asia-Iraq Islamic Bank during the time period from the first half for the year 2018 to the first half year 2020. The research relied on financial analysis tools to analyze the growth rates of Murabaha returns achieved on the amounts invested in the two researchers used the financial ratios for profitability indicators (Return On Assets Ratio (ROA) (Y1), Return on Equity Ratio (ROE) (Y2)), depending on the financial Islamic certificates of deposit (ICD) (X) of the invested bank his money in it. In addition, statements, especially the balance sheets and income statements of the bank. The two researchers concluded that the return on Murabaha Islamic certificates of deposit (ICD) contributed to the increase in the bank’s profit through the opportunities provided by these certificates for Islamic banks to invest their surplus liquidity despite their issuance in the form of Murabaha only. And these certificates increase the return on Murabaha with the increase in the period of their investment. Also, the Islamic banks’ role in Iraq was limited to buying (ICD) certificates from the central bank (CBI) without selling them to customers, and they also did not issue them for the purpose of financing economic projects. The two researchers recommended that it is possible to benefit from the experiences of the countries of the world in issuing Islamic deposit certificates in various financing formats such as speculation (Mudarabah) as in the State of Qatar and in the form of leasing (Ijara) as in Morocco and sharing (Musharakah) and others. As well as the emphasis on the Central Bank of Iraq (CBI) to issue instructions to develop the mechanism for Islamic certificates of deposit (ICD) in accordance with the followed global system, to help Islamic banks issue these certificates to finance economic projects in order to contribute to achieving economic development. And to emphasize on Islamic banks in diversifying their investment portfolios and participate in all terms of certificates, especially long term as they yield more return.